Peter M. Fischer and Teresa Bürge (eds). Sea Peoples Up-to-Date. New Research on Transformations in the Eastern Mediterranean in the 13th-11th Centuries BCE (Proceedings of the ESF-Workshop held at the Austrian Academy of Sciences, Vienna, 3-4 November 20 - Dautais, Louis (Journal of Greek Archaeology, 2020)
This volume is the outcome of an international workshop held at the Austrian Academy of Sciences in Vienna in November 2014. Since the first use of the term ‘Sea Peoples’ (People’s de la Mer) 1867 by French Egyptologist Emmanuel de Rougé, the topic has not lost its popularity, with plenty of attention in recent years, including now published workshops at Louvain-la-Neuve (in 2014) and Warsaw (in 2016). The present volume wanted to go beyond the information provided by the texts and aimed at presenting new archaeological data and their analysis, covering a wider geographical region and implying a more holistic approach than ever before. As the subtitle indicates, the specific aim of the volume is to study the various political, economic, social and cultural transformations in the Eastern Mediterranean from the 13th to 11th centuries BC that can be connected to the Sea Peoples phenomenon.